Including capabilities of local actors in regional economic development: Empirical results of local seaweed industries in Sulawesi - Vredegoor, Mark T. J.; Pennink, Bartjan W (UI Scholars Hub, 2013)
Stimson, et al. (2009) developed one of the most relevant and well known model for Regional Economic Development. This model covers the most important factors related to economic development question. However, this model excludes the social components of development. Local community should be included in terms of the development of a region. This paper introduced to the Stimson model “Skills” and “Knowledge” at the individual level for local actors indicating the capabilities at the individual level and introduced “Human Coordination” for the capabilities at the collective level. In our empirical research we looked at the Indonesian seaweed market with a specific focus on the region of Baubau. This region was chosen because there are hardly any economic developments. Furthermore this study focuses on the poorer community who are trying to improve their situation by the cultivation of Seaweed. Eighteen local informants was interviewed besides additional interviews of informants from educational and governmental institutions in the cities of Jakarta, Bandung and Yogyakarta. The informants selected had a direct or indirect relationship with the region of Baubau. With the support of the empirical data from this region we can confirm that it is worthwhile to include the local community in the model for regional economic development. The newly added variables: at the individual level; Skills and Knowledge and at the level of the collective: Human Coordination was supported by the empirical material. It is an indication that including the new variables can give regional economic an extra dimension. In this way we think that it becomes more explicit that “endogenous” means that the people, or variables closely related to them, should be more explicitly included in models trying to capture Regional Economic Development or rephrased as Local Economic Development.